Manajemen Berbasis Madrasah dalam Perspektif Manajemen Mutu Pendidikan Islam di Pondok Pesantren - Rizandi, Hidayat; Hasan, Izhar; Zulmuqim, Zulmuqim (LP2M Universitas Islam Ahmad Dahlan, 2023)
This article discusses Madrasah-Based Management in the Perspective of Quality Management of Islamic Education at the Syech Ahmad Chatib Islamic Boarding School. This research is included in qualitative research because the method used by researchers is descriptive methods. Data was obtained through observation, interviews, personal documentation and other official documentation. The research results show that the curriculum used at the Tahfizhul Quran Syech Ahmad Chatib Islamic Boarding School is the Independent Curriculum. Tahfizhul Quran Syech Ahmad Chatib Islamic boarding school has implemented curriculum evaluation strategy procedures, namely, needs evaluation, input evaluation, process evaluation, product/output evaluation. The head of the madrasah as the highest executive leader at the Tahfizhul Quran Syech Ahmad Chatib Islamic Boarding School has the task of assisting the General Chair of the Foundation and Islamic Boarding School Leaders in the management of educational staff and teaching staff which includes planning and procurement of educational staff and educators, coaching and development, assessment and dismissal.